Pattern of Diseases Presenting in ENT Outpatient Department in a Postgraduate Teaching Hospital in S.I.T.E. Area Karachi: Pattern of Diseases in ENT - Khan, Tahir Hussain; Rana, Ashfaq Hussain; Memon, Muhmmad Jamil; Rahim, Danishur; Ibrahim, Mukhtar; Siddiqui, Tariq Zia (Pakistan Journal of Health Sciences, 2024)
Ear, Nose and Throat (ENT) diseases are one of the public health problems and affect a huge number of the patient around the globe. Objective: To determine the pattern of ENT disorders or diseases in those patients who were attended outpatient department of ORL in a postgraduate teaching hospital of Karachi. Methods: Patients presenting at ENT OPD were selected randomly for the study. Data about ENT problems and information were collected through well structured questionnaire. After data collection, it was entered and analyzes by using software SPSS-23. Variables were age, sex, residence, socioeconomic status and different ENT diseases including wax, otitis media, allergic rhinitis, pharyngitis, tonsillitis, Deviated Nasal Septum (DNS) etc. Results: Male patients were 585 (46.8%) while female patients were 665 (53.2%) out of 1250 patients. Most of the patients were from industrial areas 775 (62%) and 475 (38%) were from city areas. 355 (28%) were suffering from wax followed by acute otitis media 300 (24%), acute tonsillitis and deviated nasal septum each in 225 (18%), otitis externa 150 (12%) and acute pharyngitis 145 (11%). In our study, a huge number of 72% of cases had ear disorders. 43.2% of patients had nasal issues, while 45.2% were related to laryngopharyngeal issues. Conclusions: Majority of the patients attending outpatient ENT department were related to ear wax followed by acute otitis media, acute tonsillitis, DNS, otitis externa, acute pharyngitis and many patients have multiple diseases.